Use of methods and tools for an effective small and medium-sized enterprise in Szabolcs-Szatmár-Bereg county in Hungary - Nouar, Dalila; Popovics, Péter (Applied Studies in Agribusiness and Commerce, 2022)
Small and medium-sized enterprises form the engine of the Hungarian economy, both in terms of their number and their employment rate. Therefore, the efficient operation of this sector is in the interest of many economic actors. However, experience shows that today’s SME sector still needs to develop in many ways to become efficient. This study aimed to analyze whether SMEs use the necessary methods and tools to be efficient. Planning and the development of strategy are very important methods and tools for efficient and organized work, as it defines and clarifies the direction taken by an enterprise. However, the survey and the in-depth interview showed that they are not necessarily considered important for the participating SME leaders. According to the interview, one of the reasons is that SME leaders have a better understanding of everyday tasks and their implementation than the managers of large companies. Furthermore, in most cases, the SME leader is personally involved in everyday work. This provides the advantage of having the opportunity to fully understand the enterprise, thus managing, and developing it more effectively, as he or she can intervene more flexibly, faster, and more accurately if necessary. However, due to the small size of the organization, the manager also must perform the tasks of several functions (marketing, management, finance, etc.), which require multidisciplinary knowledge and skill. In SMEs, due to their specificities, it is difficult to apply best practices in large enterprises in both management and various functions. JEL code: M21